Retand: a novel family of gypsy-like retrotransposons harboring an amplified tandem repeat - Kejnovsky, Eduard; Kubat, Zdenek; Macas, Jiri; Hobza, Roman; Mracek, Jaroslav; Vyskot, Boris (Molecular genetics and genomics, 2006)
In this paper we describe a pair of novel Ty3/gypsy retrotransposons isolated from the dioecious plant Silene latifolia, consisting of a non-autonomous element Retand-1 (3.7 kb) and its autonomous partner Retand-2 (11.1 kb). These two elements have highly similar long terminal repeat (LTR) sequences but differ in the presence of the typical retroelement coding regions (gag-pol genes), most of which are missing in Retand-1. Moreover, Retand-2 contains two additional open reading frames in antisense orientation localized between the pol gene and right LTR. Retand transcripts were detected in all organs tested (leaves, flower buds and roots) which, together with the high sequence similarity of LTRs in individual elements, indicates their recent transpositional activity. The autonomous elements are similarly abundant (2,700 copies) as non-autonomous ones (2,100 copies) in S. latifolia genome. Retand elements are also present in other Silene species, mostly in subtelomeric heterochromatin regions of all chromosomes. The only exception is the subtelomere of the short arm of the Y chromosome in S. latifolia which is known to lack the terminal heterochromatin. An interesting feature of the Retand elements is the presence of a tandem repeat sequence, which is more amplified in the non-autonomous Retand-1.
Keywords: genetická transkripce; Blotting, Southern; tandemové repetitivní sekvence; retroelementy; Silene; DNA, Plant; sekvence nukleotidů; Chromosomes, Plant; telomery; Transcription Factors; Molecular Sequence Data; Transcription, Genetic; molekulární sekvence - údaje; Tandem Repeat Sequences; Terminal Repeat Sequences; Recombinant Proteins; Retroelements; Genome, Plant; Telomere; rekombinantní proteiny; Base Sequence; koncové repetice; DNA rostlinná; Southernův blotting; transkripční faktory; chromozomy rostlin; genom rostlinný